Flood Risk Mitigation: Pressing Issues and Challenges - Yazid, Ahmad Shukri; Tengku Adnan, Tengku Faris Fakhri; Abdullah, Adbullah Aziz; Wan Daud, Wan Norhayate; Salleh, Fauzilah; Husin, Mohd Rasid (International Review of Management and Marketing, 2017)
The increase number of natural disasters that struck the world gives damaging impacts to the people and properties. This paper attempts to examine crucial pressing issues and challenges in mitigating flood losses and loss of lives in Malaysia. Only qualitative approach is used to address these pressing issues and challenges of natural disaster. Kelantan is one the states in the east coast of Malaysia that experienced the highest loss of properties and infrastructure in 2014 massive flood. Semi-structured interview was designed and used to collect data from six government agencies in the state of Kelantan. These agencies were, Kelantan State Education Department (KSED), Kelantan State Department of Rescue and Fire Brigade (KDRFB), Kelantan State Health Department (KSHD), Local Authority of Kuala Krai (LAKK), Kelantan State Social and Welfare Department (KSSWD) and Kelantan State Police Contingent (KSPC). The finding of the study revealed that were eight pressing issues and four challenges. The eight pressing issues are flood preparations, lack of rescuers, lack of awareness, communication difficulty, lack of assets for rescue, transportation issues, the absence of food supply, and other constraints. On the other hand, the challenges are lack of provisions, redevelopment, the social and economic situation, and trauma. These pressing issues and challenges need to be seriously addressed by the State and Federal level of Government of Malaysia so that future natural disaster like the 2014 flood can be managed in a much more prepared way or manner. Keywords: Disaster Risk Reduction, Natural Disaster, Flood, National Security Council Directive 20, Malaysia, Pressing Issues, Challenges JEL Classifications: F52, H84, Q54